2012
DOI: 10.2147/ijn.s33709
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface coating and particle size on the uptake of small and ultrasmall superparamagnetic iron oxide nanoparticles by macrophages

Abstract: Purpose: Magnetic resonance imaging (MRI) using contrast agents like superparamagnetic iron oxide (SPIO) is an extremely versatile technique to diagnose diseases and to monitor treatment. This study tested the relative importance of particle size and surface coating for the optimization of MRI contrast and labeling efficiency of macrophages migrating to remote inflammation sites. Materials and methods:We tested four SPIO and ultrasmall superparamagnetic iron oxide (USPIO), alkali-treated dextran magnetite (ATD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Phagocytosis and receptor-mediated endocytosis are important for uptake of larger particles, whilst smaller particles are internalized by pinocytosis. Although the avidity of macrophage uptake is strongly influenced by particle size and charge, the surface coating is particularly important [ 8 , 9 ]. As a result of their smaller size, USPIOs are less readily recognized by phagocytic cells and persist in the circulation for longer than other iron particles (plasma half-life 14–30 h in humans) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytosis and receptor-mediated endocytosis are important for uptake of larger particles, whilst smaller particles are internalized by pinocytosis. Although the avidity of macrophage uptake is strongly influenced by particle size and charge, the surface coating is particularly important [ 8 , 9 ]. As a result of their smaller size, USPIOs are less readily recognized by phagocytic cells and persist in the circulation for longer than other iron particles (plasma half-life 14–30 h in humans) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“… 11 There are so many studies on the improvement of the specificity of SPIO to expand their use in biomedical applications. 9 , 10 The new SPIO we used in this study showed a transient decrease of signal intensity in the liver and blood vessels, and we found no accumulation of the new SPIO in lymphatic tissues ( Figs. 1 , 2 ).…”
Section: Discussionmentioning
confidence: 58%
“…Many previous studies have aimed to improve the unique physicochemical and biological properties of SPIO by modifying particle structure, size and coating. 8 , 9 In order to improve the properties for the applications such as drug targeting and tissue or organ imaging other than liver, it is extremely important to avoid the nonspecific uptake of SPIO by peripheral macrophages as well as by MPS and RES, which could increase the half-life of the particles in the blood. 10 , 11 Ohno et al reported that their synthetic technique renders the ferric oxide particle stealthy: only very limited amounts are absorbed by phagocytes.…”
Section: Introductionmentioning
confidence: 99%
“…To enable their enhanced detection using noninvasive MRI, macrophages labeling was performed using amine-modified PEGylated dextran-coated iron oxide nanoparticles that were checked for biocompatibility before their in vivo administration. It is well known that the size and the surface charge of SPIO nanoparticles govern cellular internalization and their distribution [24] , [25] . In line with previous studies [20] , [26] , the SPIO nanoparticles with an overall size in the range of 100 nm allowed better internalization with optimal biocompatibility in this study.…”
Section: Discussionmentioning
confidence: 99%